THE INFLUENCE OF PRODUCT QUALITY, PRICE AND BRAND IMAGE ON CONSUMER SATISFACTION AT THE MALIKA CAKE & BAKERY SHOP, ULEGLE BRANCH - Maulidayani; Sarah Nadia; Husniati; Juanita; Mirza (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
Consumer satisfaction is essential for every company, especially in the light food industry. The main factors that drive consumer satisfaction are product quality, price, and brand image. Therefore, business owners, particularly in the culinary field, are expected to pay attention to these satisfaction-driving factors. The purpose of this study is to determine the influence of product quality, price, and brand image on consumer satisfaction at Malika Cake & Bakery Ulee Gle branch. This research uses a quantitative approach with an empirical study type. The sampling technique used in this study is accidental sampling with 100 respondents. Primary data was collected through questionnaires, and secondary data was obtained from journals and books. The data analysis techniques used are descriptive analysis and multiple linear regression analysis, classic assumption tests (normality, multicollinearity, heteroscedasticity), instrument tests (validity and reliability), and hypothesis testing (F-test and T-test) using SPSS version 20.0.The results of this study indicate that product quality (X1), price (X2), and brand image (X3) have a positive and significant influence on consumer satisfaction (Y).High product quality is achieved through quality raw materials, standardized production processes, and modern technology, while competitive pricing is determined by efficient cost management and adaptive pricing strategies. A strong brand image is formed from good customer service, continuous product innovation, and targeted marketing approaches. These factors not only increase consumer satisfaction but also strengthen the loyalty and competitiveness of Malika Cake &Bakery.